Effect of Alkalization Duration and the Orientation of Fiber on Composites of Polyester Reinforced Fibre of Terap Tree (Artocarpus Elasticus) on Impact and Bending Strength - Syarif, Akhmad; Sumantri, Dhenny; Robittah, Ahmad; Prayogi, Syafa'at (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2022)
Composite application has increased in recent years due to many advantages, e.g. In Kalimantan, there are many types of flora, one of which is the Terap tree (Artocarpus elasticus) which has a strong enough strength and is usually used by the Dayak people as clothing, hats, and rigging. In this research, we examine the laminate composite of tree skin fibers against bending strength and impact price. In making composites using a variety of alkali time, namely 60 minutes, 90 minutes and 120 minutes, the amount of alkali concentration used is 15% of the total volume of alkaline liquid. Then also use variations of fiber orientation 0o-900-00-900, 00-900-900-00, and 900-00-00-900. The impact test results showed that the highest value was obtained in specimens with an immersion time of 90 minutes with 00-900-00-900 orientation of 0.00294 joule / mm2 and the lowest value was found in specimens with immersion time 120 minutes 00-900-00-900 amounting to 0.00164 joules / mm2. While the Bending test obtained the highest value in specimens with 120 minutes of immersion time with 00-900-00-900 fiber orientation of 48.01 mph and the lowest value was obtained in specimens with 60 minutes immersion time at 900-00-00-900 for 16.62 MPa.